Neurokine receptors and lipid rafts - Port, Martha D; Gibson, Robin M; Nathanson, Neil M (Journal of neurochemistry, 2007)
Leukemia inhibitory factor (LIF) and ciliary neurotrophic factor (CNTF) are cytokines which signal through receptor complexes that include the receptor subunits glycoprotein 130 (gp130) and the LIF receptor (LIFR), but CNTF also requires the non-signal transducing CNTF receptor (CNTFR) for binding. We show here that in IMR-32 neuronal cells endogenously expressing the receptor subunits for LIF and CNTF, CNTFR, but not gp130 or LIFR, is found in detergent-resistant lipid rafts. In addition, stimulation of these cells with CNTF resulted in a rapid translocation of a portion of gp130 and LIFR into detergent-resistant lipid rafts while an equivalent stimulation with LIF did not. Disruption of lipid rafts by cholesterol depletion of cell membranes blocked the CNTF-induced translocation of LIFR and gp130. Interestingly, while cholesterol-depletion did not inhibit signal transducer and activator of transcription 3 phosphorylation by either CNTF or LIF stimulation, it strongly inhibited both CNTF- and LIF-mediated phosphorylation of extracellular signal-regulated kinases 1 and 2 and Akt. LIF and CNTF generally appear to have redundant effects in cells responsive to both cytokines. Intriguingly, the data presented here suggest a possible mechanism whereby CNTF or other cytokines that signal through CNTFR could generate signals distinct from those elicited by cytokines such as LIF which utilize a LIFR/gp130 heterodimer, via association with or exclusion from lipid rafts.